SHORT AND LONG TERM MORTALITY RATES AFTER MAJOR LOWER LIMB AMPUTATION IN PATIENTS OLDER THAN 80 YEARS
Introduction: Mortality rates after lower limb amputation are notoriously high and age is associated with increased mortality. The aim of this retrospective study was to determine mortality rates after a first major lower limb amputation in a cohort of patients older 80 years old. Methods: We performed an analysis of factors affecting early and late outcome after major lower limb amputation for peripheral vascular disease or diabetic complications at a tertiary referral vascular center between 2008 and 2015 in patients older than 80 years old. Results: 557 patients underwent a major amputation (54% female), of median age 86.3 ± 4.4 years and 20% had bilateral amputations during the study period. Median follow-up was 4.8 [0.8; 16.4] months. 30-day and 2-year mortality rates were 27% and 77%. Age adjusted 1-year mortality rate after trans-femoral amputation (TFA) was 68%, almost double that of trans-tibial amputation (TTA) (36%, p= .04). The rate of re-operation was substantially greater after TTA (36% vs 17%, p< .01). Survival and Cox regression analysis demonstrated that long-term mortality was associated with hospital re-admission (HR: 2.00, p <.05) cerebrovascular and chronic kidney disease (HR: 1.22 and 1.24 respectively, p <.05), acute ischemic amputation (HR 1.21 p <.05). Previous revascularized amputees and TTA survived longer (HR 0.65 and 0.51 respectively, p <.01). Conclusions: This study adds prognostic information for a well-defined population of people with a first amputation at or proximal to a transtibial level, due to a vascular or a infection related cause. Mortality rates after lower limb amputation are notoriously high, with only 23% of these cohort patients living longer than two years.